Clinical characteristics and visual outcome of Vogt Koyanagi Harada disease patients in a specialized eye hospital in Nepal - Bastola Paudel, Jyoti; Manandhar, Anu; Shrestha, Smita (Journal of Nepal Health Research Council, 2025)
Background: To evaluate clinical characteristics and visual outcome of Vogt-Koyanagi-Harada disease patients in Nepal. Methods: Retrospective series of all the cases of VKH treated at Tilganga Institute of Ophthalmology from 1st July 2017 to 31st June 2022. Results: Fifty-four cases were included, 18(33.33%) were male and 36 (66.67%) were female. Mean age was 41.47±15.57 years and median age was 38 years. All cases were bilateral. Two patients had a complete presentation (3.7%), thirty an incomplete presentation (55.5%) and twenty-two had a possible syndrome (40.7%). Fortysix (85. 1%) patients presented at acute uveitic stage and eight (14.8%) presented at chronic recurrent stage. The most common extraocular finding in our patient population was headache (59.2%). Posterior segment findings included exudative retinal detachment in 40(74%), disc edema in 33(61.1%) and sunset glow fundus in 3(5.5%). Conclusions: Bilateral panuveitis is the most common ocular manifestation of VKH and majority of eyes present with exudative retinal detachment. Oral prednisone with or without immunomodulatory therapy was the primary treatment. Keywords: Immunomodulatory therapy; Nepal: panuveitis; vogt-koyanagi-harada disease.